Evolution of commercially available compounds for HTS. Issue 2 (February 2019) - Volochnyuk, Dmitriy M.; Ryabukhin, Sergey V.; Moroz, Yurii S.; Savych, Olena; Chuprina, Alexander; Horvath, Dragos; Zabolotna, Yuliana; Varnek, Alexandre; Judd, Duncan B.
Highlights: A critical assessment of 16 million commercially available compounds. A comparison of vendors' offerings. How the offerings have evolved to meet modern physiochemical requirements. A selection of 500, 000 lead-like compounds that can be sourced from just 6 suppliers. Abstract : Over recent years, an industry of compound suppliers has grown to provide drug discovery with screening compounds: it is estimated that there are over 16 million compounds available from these sources. Here, we review the chemical space covered by suppliers' compound libraries (SCL) in terms of compound physicochemical properties, novelty, diversity, and quality. We examine the feasibility of compiling high-quality vendor-based libraries avoiding complicated, expensive compound management activity, and compare the resulting libraries to the ChEMBL data set. We also consider how vendors have responded to the evolving requirements for drug discovery. Teaser: An assessment of 16 million commercially available compounds, (properties and quality), comparing vendors' offerings and how they have evolved to meet modern physiochemical requirements. A selection of 500, 000 lead-like compounds for high throughput screening.